Estimation of Undiagnosed Diabetes and Pre-diabetes in People 45–75 Years in Two Blocks of Himachal Pradesh, India: A Cross-sectional Study - Ashok Bhardwaj; Sanjay Kumar; Mitasha Singh; Chirag Goel (Amrita Journal of Medicine)
Background: As per the International Diabetes Federation guidelines and American Diabetic Association guidelines, all people above 45 and <75 years should be regularly tested for undiagnosed diabetes. Objective: We aimed to estimate the prevalence of undiagnosed diabetes and pre-diabetes in the population aged 45–75 years using fasting plasma glucose (FPG), oral glucose tolerance test (OGTT), and glycated hemoglobin (HbA1c). Materials and Methods: An observational cross-sectional study was conducted at district Hamirpur and district Una of Himachal Pradesh on 600 adults 45–75 years of age. A community-based screening was conducted using a questionnaire with symptoms suggestive of diabetes and other non-communicable diseases such as hypertensions and stroke. Already diagnosed diabetics were excluded from the second phase of the study where all patients positive on screening were invited for laboratory investigations to confirm the diabetic status. Diabetes and pre-diabetes prevalence was calculated using fasting blood glucose (FBS), OGTT, and HbA1c criteria of the World Health Organization individually. Results: Using FBS, 21.7% were found to be pre-diabetic and 15.5% were diabetic. Using OGTT on the same population, 19.7% were labeled as diabetic and 48.2% were impaired glucose-tolerant. Conclusion: The prevalence of only diabetes was highest on OGTT and lowest using FPG.